Readiness of Science Education Teachers for Online Teaching Internship - Andrea Paula Malawi; Christine O. Panilag; Mark Ian Joseph A. Redelosa; Bianca Ricablanca; Joje Mar P. Sanchez (Jurnal Pendidikan Indonesia, 2026)
The development of online and hybrid learning poses new challenges for teacher education programs in preparing prospective Science teachers for virtual teaching practice. This study aims to analyze the readiness of fourth-year Science education students for online teaching internships based on their technological, academic, and pedagogical competencies. This study used a mixed-methods approach with a sequential explanatory design. The study subjects consisted of 63 Science education students. Data were collected through questionnaires, achievement tests, and semi-structured interviews using instruments such as readiness questionnaires, academic ability tests, and interview guidelines. Data were analyzed using descriptive statistics, chi-square tests, and thematic analysis. The results showed that students had good technological competencies, consistent academic achievement in core science domains, and pedagogical readiness in lesson planning, implementation of learning strategies, classroom management, and online assessment. However, challenges were still encountered related to access to resources, mastery of specific material, and balancing responsibilities during online internships. This study concluded that Science education students are generally ready to undertake online teaching internships if supported by adequate guidance, institutional facilities, and independent learning opportunities. The implications of this research suggest that teacher education institutions need to integrate digital pedagogy, strengthen professional development, and provide ongoing mentoring to support the readiness of prospective Science teachers in online learning.